Understanding Kazuo Ishiguro - Shaffer, Brian W., 1960- (Understanding contemporary British literature., 1998)
"In Understanding Kazuo Ishiguro, Brian W. Shaffer provides the first critical survey of the life and work of the Booker Prize-winning author of The Remains of the Day. One of the most closely followed British writers of his generation, the Japanese-born, English-raised and -educated Ishiguro is the author of four critically acclaimed novels: A Pale View of Hills (1982, Winifred Holtby Prize of the Royal Society of Literature), An Artist of the Floating World (1986, Whitbread Book of the Year Award), The Remains of the Day (1988, Booker Prize), and The Unconsoled (1995, Cheltenham Prize)." "Shaffer's study reveals Ishiguro's novels to be intricately crafted, psychologically absorbing, hauntingly evocative works that betray the author's grounding not only in the literature of Japan but also in the great twentieth-century British masters - Joseph Conrad, Ford Madox Ford, E.M. Forster, and James Joyce - as well as in Freudian psychoanalysis. All of Ishiguro's novels are shown to capture first-person narrators in the intriguing act of revealing - yet also of attempting to conceal beneath the surface of their mundane present activities - the alarming significance and troubling consequences of their past lives."--Jacket